EVALUATION OF SOME MICROSCOPIC TECHNIQUES FOR DETECTING BILHARZIA AND INTESTINAL PARASITES - Afifi, Azzam; Ahmed, Abdel-Aziz; Sulieman, Yassir; Mohamed, Zakaria; Pengsakul, Theerakamol (International Journal of Research -GRANTHAALAYAH, 2016)
The objective of the present study was to evaluate the efficacy of five different diagnostic techniques (haematouria, macro-haematouria, syringe filtration, vacuum flask filtration and sedimentation) in the detection of urinary schistosomiasis. Likewise, five techniques (direct smear, cellophane thick smear, ether-formalin, modified Kato-template and modified Kato-syringe) techniques used in the detection of intestinal schistosomiasis and other intestinal parasites were evaluated using fecal samples. The results showed that the most efficient diagnostic technique for fecal samples is the modified Kato-Katz technique, while the ether-formalin method was the most sensitive tool for the detection of Schistosoma mansoni, Enterobius sp. and Ascaris sp. rates of infection and worm burden. The modified Kato techniques (template and syringe) failed to detect the intestinal protozoa, Giardia lamblia and Entamoeba histolytica, while the syringe filtration technique was the most powerful urine test.